A novel Smac mimetic APG-1387 demonstrates potent antitumor activity in nasopharyngeal carcinoma cells by inducing apoptosis. Issue 1 (10th October 2016) - Li, Ning; Feng, Lin; Han, Hui-Qiong; Yuan, Jing; Qi, Xue-Kang; Lian, Yi-Fan; Kuang, Bo-Hua; Zhang, Yu-Chen; Deng, Cheng-Cheng; Zhang, Hao-Jiong; Yao, You-Yuan; Xu, Miao; et al.
Highlights: APG-1387 plus TNF-α has a potent in vitro antitumor effect on NPC cells. The in vitro antitumor effect was RIPK1-dependent. Inhibition of NF-κB or AKT pathway can sensitize the resistant NPC cells to APG-1387. In vivo, APG-1387 displays antitumor activity at well-tolerated doses. Abstract: Despite advances in the development of radiation against nasopharyngeal carcinoma (NPC), the management of advanced NPC remains a challenge. Smac mimetics are designed to neutralize inhibitor of apoptosis (IAP) proteins, thus reactivating the apoptotic program in cancer cells. In this study, we investigated the effect of a novel bivalent Smac mimetic APG-1387 in NPC. In vitro, APG-1387 in combination with TNF-α potently decreased NPC cell viability by inducing apoptosis in majority of NPC cell lines. The in vitro antitumor effect was RIPK1-dependent, whereas it was independent on IAPs, USP11, or EBV. Of note, the inhibition of NF-κB or AKT pathway rendered resistant NPC cells responsive to the treatment of APG-1387/TNF-α. In vivo, APG-1387 displayed antitumor activity as a single agent at well-tolerated doses, even in an in vitro resistant cell line. In summary, our results demonstrate that APG-1387 exerts a potent antitumor effect on NPC. These findings support clinical evaluation of APG-1387 as a potential treatment for advanced NPC.